The shelterin component TRF2 mediates columnar stacking of human telomeric chromatin - Wong, Sook Yi (2024)
Telomere repeat binding factor 2 (TRF2) is an essential component of the telomeres and also plays an important role in a number of other non-telomeric processes. Detailed knowledge of the binding and interaction of TRF2 with telomeric nucleosomes is limited. Here, we study the binding of TRF2 to in vitro-reconstituted kilobasepair-long human telomeric chromatin fibres using electron microscopy, single-molecule force spectroscopy and analytical ultracentrifugation sedimentation velocity. Our electron microscopy results revealed that full-length and N-terminally truncated TRF2 promote the formation of a columnar structure of the fibres with an average width and compaction larger than that induced by the addition of Mg2+, in agreement with the in vivo observations. Single-molecule force spectroscopy showed that TRF2 increases the mechanical and thermodynamic stability of the telomeric fibres when stretched with magnetic tweezers. This was in contrast to the result for fibres reconstituted on the 'Widom 601' high-affinity nucleosome positioning sequence, where minor effects on fibre stability were observed. Overall, TRF2 binding induces and stabilises columnar fibres, which may play an important role in telomere maintenance.